Penyebab Terjadinya Konflik Ukraina-Rusia - Novitasari (Jurnal Pustaka Cendekia Pendidikan, 2024)
This research uses a literature review or research method by collecting source materials and theories on relevant topics. The aim of this research is to determine the causes of the conflict between Russia and Ukraine. The results of the discussion showed that the reason Ukraine was attacked by Russia was because of Ukraine's desire to join NATO, so the dispute was resolved by force or by force through war. NATO's actions in responding to this became a threat to Russia which ultimately worsened the conflict on the Ukrainian border. Apart from that, there was the incident of Russian intervention in Crimea (Ukraine). Intervention is the act of interfering with a country in the internal affairs of another country. The background of Russia's intervention into Ukrainian territory was at the request of the President of Ukraine, Viktor Yanukovych with the intention of helping resolve Ukraine's internal conflict, especially in the Crimea region. Russia's intervention was carried out by sending Russian military troops aimed at helping stop the internal conflict in Ukraine, but this action actually developed and did not meet its objectives. These interventions include, among other things, occupying military forces by Russia, holding a referendum in Crimea, as well as providing military support and assistance to separatist groups that threaten the sovereignty, security and territorial integrity of Ukraine, especially in Crimea.